Unveiling the functional diversity of the alpha/beta hydrolase superfamily in the plant kingdom - Mindrebo, Jeffrey T; Nartey, Charisse M; Seto, Yoshiya; Burkart, Michael D; Noel, Joseph P (Current opinion in structural biology, 2016)
•Alpha/beta hydrolases play key roles in plant primary and specialized metabolism.•Unexpected catalytic functions for alpha/beta hydrolases found in plants.•Plant kingdom adapted alpha/beta hydrolases as hormone receptors.•Alpha/beta hydrolase superfamily is sparsely characterized in plants. The alpha/beta hydrolase (ABH) superfamily is a widespread and functionally malleable protein fold recognized for its diverse biochemical activities across all three domains of life. ABH enzymes possess unexpected catalytic activity in the green plant lineage through selective alterations in active site architecture and chemistry. Furthermore, the ABH fold serves as the core structure for phytohormone and ligand receptors in the gibberellin, strigolactone, and karrikin signaling pathways in plants. Despite recent discoveries, the ABH family is sparsely characterized in plants, a sessile kingdom known to evolve complex and specialized chemical adaptations as survival responses to widely varying biotic and abiotic ecologies. This review calls attention to the ABH superfamily in the plant kingdom to highlight the functional adaptability of the ABH fold.